Carl Goerdeler and the Jewish question, 1933 - 1942 - Hoffmann, Peter 1930-2023 (Cambridge University Press, 2011)
"Using new evidence and thus far under-researched documents, this book describes the actions of Carl Goerdeler, the German resistance leader who consistently engaged in efforts to protect the Jews against persecution"--